Letter from James Curtis Booth to President Grover Cleveland - Booth, James Curtis (1887)
James Curtis Booth (1810-1888) sends president Grover Cleveland (1837-1908) a copy of Booth's resignation from his official position at the United States Mint.
Keywords: Booth, James Curtis, 1810-1888; United States Mint; Mint of the United States; Cleveland, Grover, 1837-1908; Resignation